2013
DOI: 10.1590/s1516-89132013000300012
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of the spectroscopic profile of the sugar fraction of apple pomace

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Sucrose was the most variable component in amount as the variation coefficient calculated from the contents in the 11 cultivars was 73.4 %. A study using an NMR-based method for quantitative determination reported constant relative proportions in four cultivars, which was fructose > glucose > sucrose [27].…”
Section: Mono-and Disaccharidesmentioning
confidence: 99%
“…Sucrose was the most variable component in amount as the variation coefficient calculated from the contents in the 11 cultivars was 73.4 %. A study using an NMR-based method for quantitative determination reported constant relative proportions in four cultivars, which was fructose > glucose > sucrose [27].…”
Section: Mono-and Disaccharidesmentioning
confidence: 99%
“…FTIR and multivariate analysis have also been used to correlate the sugar composition of apricots and mangos with their ripeness state (Duarte and others ; Bureau and others ), to classify citrus juices (Hirri and others ), or to determine adulteration in pomegranates (Vardin and others ), apple, orange, and peach juices (Sivakesava and others ; Leopold and others ) and the composition of apple pomaces (Queji and others ; Gabriel and others ). In strawberries, FTIR has been employed to discriminate fruits and leaves from different cultivars (Kim and others ) or to determine the thermophysical properties of FOS during postharvest storage (Blanch and others ).…”
Section: Introductionmentioning
confidence: 99%
“…The peaks in the region of 2.35 to 1.66 ppm are assigned to H2–H6 in α and β‐glucose (Figure S4, Supporting Information). [ 25 ] The anomerization between α and β‐glucose has been reported in aqueous acid solutions. [ 26 ] With the increase of glucose concentration, the glucose 1 H signals shifted upfield because of the increased magnetic shielding of each proton as a result of coordination of glucose with H 3 O + via hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%